Providing Web Search Capability for Low-Connectivity Communities - Levison, Libby; Thies, Bill; Amarasinghe, Saman (International Symposium on Technology and Society. Raleigh, North Carolina., 2002)
There are many technical problems that exist in communities other than our own. These problems both deserve our attention and require focused research. We present one example: the TEK Search Engine. TEK is an email-based search engine designed to deliver low bandwidth information to low-connectivity communities.